Weak and very weak solutions of the Laplace equation and the Stokes system with prescribed regularity - Apel, Thomas; Lorenz, Katharina; Nicaise, Serge (Examples and counterexamples, 2025)
To verify theoretical results it is sometimes important to use a numerical example where the solution has a particular regularity. The paper describes one approach to construct such examples. It is based on the regularity theory for elliptic boundary value problems.